"Design and Implementation of cloud services by using Python ": "Design and Implementation of cloud services by using Python " (International Journal of Engineering and Computer Science, 2018)
Cloud Computing DEF: Cloud Computing is a virtualized compute power and storage delivered via platform-agnostic infrastructures of abstracted hardware and software accessed over the Internet. On Client Requirement, IT resources,  are generated and willing of efficiently, are dynamically scalable through a verity of programmatic interfaces and are billed variably based on measurable usage. Cloud computing is a general term for anything that involves delivering hosted services over the Internet. These services are broadly divided into three categories: Infrastructure-as-a-Service (IaaS), Platform-as-a-Service (PaaS) and Software-as-a-Service (SaaS).Cloud applications are developed in Platforms as a Service following the PaaS architecture imposed by several providers. We find in the literature some works describing frameworks and architectures for cloud software development by using Python scripting language, but there is a lack of a generic methodology which covers the whole application development lifecycle nowadays Python place Big Roles to maintain Big Data and Best Cloud services to the client. I  want to introduce all best methodology to implementing all database,  front-end design and maintains and back-end services of PaaS model by using on language i.e. PYTHON.